Find the sum of the zeros of a polynomial
x2–x–4.
Answers
Answered by
4
Answer:
1
Step-by-step explanation:
Quadratic equation is given by x^2 - (sum of zeros) x + (product of zeros)
Answered by
2
Find the sum of the zeroes of a polynomial
Factorise
We have,
Zeroes of Quadratic equation is
=>![\frac{ - b ± \sqrt{ {b}^{2} - 4ac} }{2a} \frac{ - b ± \sqrt{ {b}^{2} - 4ac} }{2a}](https://tex.z-dn.net/?f=+%5Cfrac%7B+-+b+%C2%B1+%5Csqrt%7B+%7Bb%7D%5E%7B2%7D++-+4ac%7D+%7D%7B2a%7D+)
So,
=>![x = \frac{ - ( - 1) ± \sqrt{ {( - 1)}^{2} - 4(1)( - 4) } }{2(1)} x = \frac{ - ( - 1) ± \sqrt{ {( - 1)}^{2} - 4(1)( - 4) } }{2(1)}](https://tex.z-dn.net/?f=x+%3D++%5Cfrac%7B+-+%28+-+1%29+%C2%B1++%5Csqrt%7B+%7B%28+-+1%29%7D%5E%7B2%7D+-+4%281%29%28+-+4%29+%7D+%7D%7B2%281%29%7D+)
=>![\frac{1 ± \sqrt{1 + 16} }{2} \frac{1 ± \sqrt{1 + 16} }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B1+%C2%B1++%5Csqrt%7B1+%2B+16%7D+%7D%7B2%7D+)
=>![\frac{1 ± \sqrt{17} }{2} \frac{1 ± \sqrt{17} }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B1+%C2%B1++%5Csqrt%7B17%7D+%7D%7B2%7D+)
=>![\frac{1 + \sqrt{17} }{2} \frac{1 + \sqrt{17} }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B1+%2B++%5Csqrt%7B17%7D+%7D%7B2%7D+)
And
=>![\frac{1 - \sqrt{17} }{2} \frac{1 - \sqrt{17} }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B1+-++%5Csqrt%7B17%7D+%7D%7B2%7D+)
Sum of zeroes is
=![\frac{1 + \sqrt{17} }{2} + \frac{1 - \sqrt{17} }{2} \frac{1 + \sqrt{17} }{2} + \frac{1 - \sqrt{17} }{2}](https://tex.z-dn.net/?f=+%5Cfrac%7B1+%2B++%5Csqrt%7B17%7D+%7D%7B2%7D++%2B++%5Cfrac%7B1+-++%5Csqrt%7B17%7D+%7D%7B2%7D+)
=>![\frac{2}{2} = 1 \frac{2}{2} = 1](https://tex.z-dn.net/?f=+%5Cfrac%7B2%7D%7B2%7D++%3D+1)
Sum of zeroes of x²-x- 4 = 1
Similar questions